Um estudo sobre use-after-free no kernel Linux - Sunbali, Yuri Said (Universidade Federal de São Carlos, 2026)
Given the growing relevance of specific vulnerability classes—and the emerging techniques and paradigms for exploiting them—there is currently a lack of in-depth, detailed studies addressing these topics. Accordingly, this work aims to contribute to current system security research by examining the Use-After-Free (UAF) vulnerability class—which has consistently proven significant for discussing emerging exploitation techniques—through a case study involving the Linux kernel and a deliberately vulnerable module.
A study on user-after-free in the Linux kernel
Keywords: Sistemas Operacionais; Linux kernel; Use-After-Free; Cibersegurança; Pesquisa de Vulnerabilidades; Desenvolvimento de Exploits; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; 9. Indústria, Inovação e Infraestrutura